The effect of leadership, motivation and organizational culture on performance of employees in the governance section of the regional secretariat of kerinci district - Wazirman Wazirman; Reko Saputra; Rengki Rengki; Anton Setiawan; Rike Irmaningsih (Global Econedu, 2021)
This study aims to see the effect of (1) Leadership on Employee Performance in the Administration Section of the Kerinci Regency Regional Secretariat (2) Motivation on Employee Performance in the Kerinci Regency Regional Secretariat Governance Section (3) Organizational Culture on Employee Performance in the Kerinci Regency Regional Secretariat Governance Section (4) Leadership, Motivation and Organizational Culture influence together on the Performance of the Employees of the Regional Secretariat of the Kerinci District Administration. Population and sample in this studywhole There are 32 employees of the Regional Secretariat of Kerinci Regency. The results of this study indicate that (1) Leadershiphas a positive significant effect on the performance of the Kerinci Regency Government Administration Section Employees (2) Motivation provide a positive influence on the performance of the Kerinci Regency Government Administration Section Employees (3) Organizational culture provide a positive influence on the performance of the Kerinci Regency Government Administration Section Employees (4) Leadership, Motivation and Organizational Culture jointly have a positive effect on the performance of employees of the Regional Secretariat of Kerinci District Administration.